Day 2 Wed, October 01, 2014 2014
DOI: 10.2118/171594-ms
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Proppant Distribution Effect on Well Productivity and Recovery Factor of Hydraulically Fractured Unconventional Reservoirs

Abstract: The most common completion methodology the industry uses to help maximize productivity and fluid recovery in unconventional reservoirs consists of placing multiple, optimally spaced transverse fractures in horizontal wells, navigating along the direction of minimum principle horizontal stress. In this type of completion, well productivity and fluid recovery can be maximized when the following conditions are met: Horizontal wellbore navigates optimally in the reservoir. Generated fracture connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…An extensive review of over 100 fractured fields was performed by Allan and Qing Sun (2003) that found typical oil recoveries for Type II/III solution gas drive reservoirs between 1525% and total average Type II/III recoveries between 20-30%. Work by Aguilera (1999) establishes Type II/III gas recoveries at 75-85%, which is similar to modeling by Sierra et al (2014) that predicts, given optimal completion strategies, shale gas recoveries of up to 70% can be achieved (Figure 1). The power of this exercise is to validate that further recovery enhancement can be achieved by implementing multi-zone (staggered) lateral placement.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…An extensive review of over 100 fractured fields was performed by Allan and Qing Sun (2003) that found typical oil recoveries for Type II/III solution gas drive reservoirs between 1525% and total average Type II/III recoveries between 20-30%. Work by Aguilera (1999) establishes Type II/III gas recoveries at 75-85%, which is similar to modeling by Sierra et al (2014) that predicts, given optimal completion strategies, shale gas recoveries of up to 70% can be achieved (Figure 1). The power of this exercise is to validate that further recovery enhancement can be achieved by implementing multi-zone (staggered) lateral placement.…”
Section: Introductionsupporting
confidence: 62%
“…This suggests that the assumption of a dynamic recovery factor is fundamentally related to fracture geometry, stimulation effectiveness and reservoir (net pay) height. Published examples of recovery factors in unconventional shale gas and oil reservoirs is limited, with authors attempting to predict it through various modeling techniques (Wan et al, 2013, Sierra et al, 2014. As such, it was decided to use naturally fractured reservoirs with similar matrix permeabilities as analogs to gain insight into the potential range and limits of recoveries.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery factor (RF), or the recoverable amount of hydrocarbon initially in place, is typically optimized in unconventional reservoirs by ideal placement of the horizontal wellbore in the reservoir, fracture connectivity to the entire productive pay zone, effectively spaced transverse fractures, and well-distributed proppant within the created fracture (Sierra et al, 2014). Prior to the optimization runs, the initial oil and gas recovery factors were both 12% for the Zipper well case as calculated by Equations 7.1 and 7.2:…”
Section: Recovery Factormentioning
confidence: 99%
“…15,16 During long-term oil and gas production, the distribution of proppants in fractures directly controls the residual aperture and permeability of hydraulic fractures, which impacts the productivity and financial advantages of hydrocarbon development. [17][18][19] Countless computational and experimental investigations have been carried out continually to uncover the impact of proppant distribution on fracture permeability and conductivity. However, millimeter-scale fractures filled with proppants are used as research objects in a portion of numerical simulation.…”
Section: Introductionmentioning
confidence: 99%